CFD modelling of vegetation barrier effects on the reduction of traffic-related pollutant concentration in an avenue of Pamplona, Spain. (July 2019) - Santiago, Jose-Luis; Buccolieri, Riccardo; Rivas, Esther; Calvete-Sogo, Hector; Sanchez, Beatriz; Martilli, Alberto; Alonso, Rocio; Elustondo, David; Santamaría, Jesús M.; Martin, Fernando
Highlights: Vegetation barriers in an open-road can be effective to mitigate air pollution. Aerodynamic and deposition effect of hedges and trees barriers are simulated. The presence of trees is crucial to reduce pollutant concentrations. Wider and taller hedges are usually more effective. The most effective leaf area density of hedges depends on deposition velocity. Abstract: With the objective of reducing population exposure, vegetation barriers composed by hedges and/or trees are usually located near roads to protect pedestrians from traffic-related pollutants. The main objective of this study is to quantify the effectiveness of this type of barriers. Black Carbon (BC) is used an indicator of the effectiveness of vegetation barrier and its concentration reduction behind the barrier is studied. Computational Fluid Dynamics (CFD) modelling, previously validated against BC experimental data across a vegetation barrier located in an avenue of Pamplona (Spain), is applied to simulate different barrier configurations. Additionally, the contribution of each vegetation effect (aerodynamic and deposition) on this reduction, as well as its sensitivity to different deposition velocities, are investigated. Results show barriers with hedge and trees are effective to locally reduce BC concentrations and suggest that the presence of trees is more crucial in reducing concentration rather than the hedge size or density. At 15 m from road in the presence of a row of trees and a 2 m-height and 2 m-width hedge the average concentration reduction percentage ranges between 45% and 66% (depending on deposition velocity) with respect to the case without vegetation barrier.